Origin and Demographic History of Philippine Pigs Inferred from Mitochondrial DNA - Layos, John King N.; Godinez, Cyrill John P.; Liao, Lawrence M.; Yamamoto, Yoshio; Masangkay, Joseph S.; Mannen, Hideyuki; Nishibori, Masahide (Frontiers in Genetics, 2022)
The Philippines is a mega-diverse country that lies at the crossroads of past human migrations in the Asia-Pacific region and is believed to have never been connected to the Asian continent, even during the major sea-level subsidence of the Quaternary. As a result, the history of pig dispersal in the Philippines remains controversial, due to limited molecular studies and absence of archaeological evidence of pig domestication. This study provides the first comprehensive analysis of 184 complete mitochondrial DNA D-loop region from Philippine pigs to elucidate their early dispersal history by performing a phylogenetic comparison with wild boars and domestic pigs worldwide. The results showed a demographic signal of the ancestry of Philippine pigs that had a close genetic relationship with those from the mainland Southeast Asia and Northeast Asia, suggesting gene flow that may have resulted from human migration and trade. Here we have suggested two possible dispersal routes. One parallels the Neolithic expansion in Island Southeast Asia and Oceania via Northeast Asia, the other from the mainland Southeast Asia, into Palawan and Sulu Archipelago as early as prehistoric times via the Sundaic Region. Despite geographic barriers to migration, numerous genetic lineages have persisted across the Philippine islands, even justifying the recognition of a Philippine Lanyu subclade. The prehistoric population history suggests a demographic expansion that coincided with the interglacial periods of the Pleistocene and may have spread from the southern regions into the eastern and central regions of the Philippines. The intriguing signal of discrepancy discovered between the ancestral pattern and distribution range of the numerous endemic Philippine wild pigs opens a challenging new approach to illuminate complexity among these animals. Our study has contributed significantly towards completing the sparse molecular studies on Philippine pigs, an essential for creating win-win conservation measures.